SOCIAL AND CULTURAL CHANGES ON THE DEVELOPMENT OF COMMUNICATION TECHNOLOGY - Loso Judijanto; Jimmy Nganta Ginting; Sastra Wandi Nduru (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
The development of communication technology, including the internet, social media and instant messaging applications, has brought about significant transformations in social and cultural dynamics. This research aims to examine the impact of communication technology on changes in social interaction, information dissemination, and cultural preservation. The research results show that this technology expands social networks without geographic boundaries and accelerates the dissemination of information, but also raises challenges such as the digital divide and threats to traditional culture. On the one hand, communication technology can be an effective means of preserving and promoting local culture; on the other hand, conscious efforts are needed to maintain cultural identity from the homogenous influence of globalization. This research suggests that collaboration between stakeholders, such as government, the private sector, and society, is critical to managing challenges and maximizing the benefits of developments in communications technology. By presenting a holistic approach, we can ensure that this transformation has a positive impact on all levels of society in social and cultural aspects.